Graduates: occupation in accordance with major - V. . Gurtov; L. . Serova; E. Fedorova (Высшее образование в России)
The article provides the analysis of the results of the sociological poll devoted to the graduates’ job placement in accordance with their major within two-three years aftergraduation. Such indices as “occupation in accordance with the major”, motivation mechanisms, territorial mobility, education prospects, vocational training level were explored on the basisof graduates’ self-appraisals.